Statistical analysis and degradation pathway modeling of photovoltaic minimodules with varied packaging strategies - Nalin Venkat, Sameera; Yu, Xuanji; Liu, Jiqi; Wegmueller, Jakob; Jimenez, Jayvic Cristian; Barcelos, Erika I.; Aung, Hein Htet; Li, Xinjun; Jaubert, Jean-Nicolas; French, Roger H.; Bruckman, Laura S. (Frontiers in Energy Research, 2023)
Degradation pathway models constructed using network structural equation modeling (netSEM) were used to study degradation modes active in photovoltaic (PV) system variants in exposure conditions of high humidity and temperature. The data-driven modeling technique enables the exploration of pairwise relationships between variables as well as multiple regression equations in which numerous degradation modes impact the variants in a simultaneous fashion. An extensive study protocol has been implemented in this work and statistical analysis was performed using 83.4 and 95 % confidence intervals to compare minimodule variants. Durable and degrading variants have been identified through the degradation pathways and statistical analysis. By using domain knowledge, statistics, and the data-driven netSEM technique, it was observed that glass/backsheet PV minimodules had power loss primarily due to corrosion.